Xanthan gum derivatives: review of synthesis, properties and diverse applications. Issue 45 (21st July 2020) - Patel, Jwala; Maji, Biswajit; Moorthy, N. S. Hari Narayana; Maiti, Sabyasachi
Abstract : Due to presence of hydroxy and carboxy functional groups, xanthan gum is amenable to various chemical modification for producing derivatives such as carboxymethyl xanthan and carboxymethyl hydroxypropyl xanthan with desirable properties for end use. Abstract : Natural polysaccharides are well known for their biocompatibility, non-toxicity and biodegradability. These properties are also inherent to xanthan gum (XG), a microbial polysaccharide. This biomaterial has been extensively investigated as matrices for tablets, nanoparticles, microparticles, hydrogels, buccal/transdermal patches, tissue engineering scaffolds with different degrees of success. However, the native XG has its own limitations with regards to its susceptibility to microbial contamination, unusable viscosity, poor thermal and mechanical stability, and inadequate water solubility. Chemical modification can circumvent these limitations and tailor the properties of virgin XG to fulfill the unmet needs of drug delivery, tissue engineering, oil drilling and other applications. This review illustrates the process of chemical modification and/crosslinking of XG via etherification, esterification, acetalation, amidation, and oxidation. This review further describes the tailor-made properties of novel XG derivatives and their potential application in diverse fields. The physicomechanical modification and its impact on the properties of XG are also discussed. Overall, the recent developments on XG derivatives are very promising to progress further with polysaccharide research.